2018
DOI: 10.3390/molecules23123365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pinocembrin as an Anti-Glycation Agent and α-Glucosidase Inhibitor from Fingerroot (Boesenbergia rotunda): The Tentative Structure–Activity Relationship towards MG-Trapping Activity

Abstract: Diabetes mellitus (DM) is a disease that is caused by a malfunction of carbohydrate metabolism, which plays an important role in the development of long-term diabetic complications. The excess glucose can be transformed to methylglyoxal (MG), a potential precursor of glycation. Glycation is a spontaneous non-enzymatic reaction that initially yields advanced glycation end-products (AGEs), which ultimately triggers several severe complications. Therefore, the inhibition of AGEs formation is the imperative approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The inhibition of DPPIV to increase the half-life of GLP1 and stimulation of the peripheral response to insulin-thereby increasing the overall effects of the GLP1-insulin signaling-has also been reported [31]. Different reports have also described the inhibitory potentials of polyphenols as potent inhibitors of specific targets related to type 2 diabetes physiopathology, including protein tyrosine phosphatase 1B (PTP1B), DPPIV, and sodium-glucose cotransporter 2, among many other targets [32][33][34]. The oral administration of ferulic acid (50 mg/kg) has been reported to significantly decrease blood glucose levels and increase plasma insulin levels in type 2 diabetic mice by elevating hepatic glycogen synthesis and glucokinase activity [31].…”
Section: Discussionmentioning
confidence: 97%
“…The inhibition of DPPIV to increase the half-life of GLP1 and stimulation of the peripheral response to insulin-thereby increasing the overall effects of the GLP1-insulin signaling-has also been reported [31]. Different reports have also described the inhibitory potentials of polyphenols as potent inhibitors of specific targets related to type 2 diabetes physiopathology, including protein tyrosine phosphatase 1B (PTP1B), DPPIV, and sodium-glucose cotransporter 2, among many other targets [32][33][34]. The oral administration of ferulic acid (50 mg/kg) has been reported to significantly decrease blood glucose levels and increase plasma insulin levels in type 2 diabetic mice by elevating hepatic glycogen synthesis and glucokinase activity [31].…”
Section: Discussionmentioning
confidence: 97%
“…Reactive carbonyl species in the glycation process, such as 3-deoxyglucosone, glyoxal, and MG, play a critical role in mediating glycation stress in human cells and are associated with various chronic diseases and cancer [41,42]. Some studies have described MG as the most important precursor for the formation of AGEs during glycation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating in vitro studies have shown that dietary flavonoids inhibit the formation of AGEs by trapping MG, the reactive dicarbonyl species precursor of AGEs [ 17 ], under physiological conditions [ 69 , 70 , 71 , 72 ]. Based on the observations on different flavonoids, compounds with the catechin-like A-ring structure showed the most potent effect on direct trapping of MG.…”
Section: Discussionmentioning
confidence: 99%